Royal Interventions in the Public Discourse on Immigration: Rhetorical Topoi on Immigration in the New Year’s Speeches of the Scandinavian Monarchs - Kjeldsen, Jens E. (Javnost-The Public, 2019)
This paper explores how the Scandinavian monarchs work through the issue of immigration in their New Year’s speeches during the years 1972–2017. Exploring immigration debate through the royal speeches provides new understanding of the issue, because the opinions of the monarch are supposed to be apolitical. Royal rhetoric is expected to embrace the whole nation, and not evoke debate. Thus, the New Year’s speeches, offer a unique insight into how identity and immigration are worked through and negotiated nationally. Comparing Denmark, Norway and Sweden is particularly revealing, because these countries share dominant traits and circumstances such as religion, institutional and political systems, common history, party dominance, size and more. In spite of this, they differ significantly in the way they deal with citizenship regulation and the way they debate immigration. Exploring how the royal speeches use different topoi and constitute nationhood and immigrants, provide an understanding for the values and moral foundations that the differences in rhetoric and regulation is built on. The study reveals that the speeches of the Danish Queen constitute Denmark as a rooted nation, the Norwegian King constitutes Norway as a rights nation, and the Swedish King constitute Sweden as an immigrant nation.